Factors influencing older nurses' decision making around the timing of retirement: An explorative mixed‐method study. (10th November 2021) - Cleaver, Karen; Markowski, Marianne; Wels, Jacques
Abstract: Aim: This study aimed to understand factors influencing decision making of older nurses around timing of retirement. Background: Global nursing shortages require flexible nurse retention strategies. Methods: An explanatory sequential mixed‐method approach: nurses across seven health care organisations within one integrated care system responded to an online survey ( n  = 524). Semistructured interviews and a focus group were conducted ( n  = 19). Results: Survey data confirmed age as a key factor influencing nurses' decision making. Factors associated with retention were flexible working conditions, financial considerations and feeling valued. Factors associated with attrition were poor or deteriorating health, stress and wish for more time with family and friends. Logit regression confirmed that flexible work patterns are the strongest predictors for working beyond retirement. Qualitative data revealed that retirement plans are accompanied by personal milestones; the work environment heavily influences these plans. Conclusions: Reasons for retirement are multifaceted, but many factors are within the control of employers. Organisational policies, practices and workplace culture have a bearing on decisions surrounding the timing of retirement. Implications for Nursing Management: Retention strategies that allow older nurses to work part‐time are key, and nurse managers need to proactively engage with older nurses to discuss their retirement plans.